Synthesis and characterization of donor-acceptor π-conjugated heterocyclic systems for nonlinear optical (NLO) and photochromic applications - Castro, Maria Cidália Rodrigues (2016)
Tese de Doutoramento em Ciências (Especialidade em Química)